Living in the south - looking at the north: The internationalization process of Sao Paulo State University in Brazil - Paula Pavarina (European Regional Science Association (ERSA), 2016)
This paper aims to present some reflections about the importance given to internationalization by Brazilian Higher Education Institutions (HEIs). In Brazil, although it is recognized as an important aspect for promoting growth and economic development, the internationalization of HE has been established in a disjointed and uneven way, and perhaps not as a strategic function established through public policies. As a former colony of Portugal, there was no attempt of establishing HE courses in Brazil until the 19th century, and institutional support given by the government began only in the 1930s. Initially there were isolated initiatives to the exchange of teachers, especially those trained in Europe. This process of internationalization, based on knowledge transfer from developed countries to Brazil, continued until 1960. From the 1960s on, Brazilian government began to establish bilateral educational, scientific and technological cooperation agreements with different countries. In the 1970s the emphasis is given to institutional programs to support graduate qualification abroad, promoting internationalization through exchange of students and development of joint research. Finally, after the 1990s, is given a strategic dimension to the internationalization of higher education, both by government and the own HEIs. In this context, there is a risk to happen a new 'international division of labor' in HE terms - division of the world between countries who send their own students abroad (the so-called 'passive' countries) and other that receive students and conduct the top research ('active' countries) in a new 'geopolitics of knowledge'. This paper presents then a case study about the internationalization process occurred in S\~ao Paulo State University (Unesp), in Brazil, evaluating both the strategic dimension (establishing agreements with foreigner HEIs and delimitation of internal rules to foster internationalization) and operational (human and material resources to perform it). Unesp is one of the leading universities in Brazil in undergraduate and postgraduate courses as well as in research, consisting of 34 university units, scattered in 24 municipalities of S\~ao Paulo. It has solid international academic cooperation agreements with over 388 foreign institutions in 59 countries and is ranked among the 500 'best' universities in the world according to the Academic Ranking of World Universities - ARWU and Times Higher Education World University Ranking. Collected data suggest that the internalization process that ocurred in Unesp reflects the general pattern observed in Brazil: the university lies in the South but looks to (and looks for) the North - to the developed countries.
Keywords: I23; I25; O15; 330; Higher Education Institutions; economic development; internationalization